2014
DOI: 10.3944/aott.2014.3184
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the anterior translation of glenohumeral joint using ultrasonography: an intra- and inter-rater reliability study

Abstract: The use of US as a measurement of ATHH has good levels of intra- and inter-rater reliability in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…SEMs reflect the extent of expected error in a measurement between the raters, 43 while CV reflects the extent of variability of the measurement score between the TR and FTF methods or raters. 43,44 Smaller CV values demonstrate less dispersion in the measurement values. 45 Previous literature has shown that a measurement tool is considered reliable if the value CV is 15% and SEMs is 5%.…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…SEMs reflect the extent of expected error in a measurement between the raters, 43 while CV reflects the extent of variability of the measurement score between the TR and FTF methods or raters. 43,44 Smaller CV values demonstrate less dispersion in the measurement values. 45 Previous literature has shown that a measurement tool is considered reliable if the value CV is 15% and SEMs is 5%.…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…The kappa values of the remaining participants were between .53 and .73, which is similar to previous studies assessing intraobserver variability for different sonographic findings in various joints. 12-15…”
Section: Discussionmentioning
confidence: 99%
“…Although no researchers have previously measured intraobserver variability on grading shoulder bursitis on US, many have reported similar intraobserver variability on different MSK-related pathologies, for different joints, and amongst different sonographic experts (both radiologists and non-radiologists). 12-15…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations